PATHOLOGICAL STUDY OF INTESTINE IN THE INDIAN BULL FROG, Hoplobatrachus tigerinus DAUDIN PARASITIZED WITH Tremiorchis ranarum (DIGENEA: PLAGIORCHIIDAE) FROM YSR DISTRICT, ANDHRA PRADESH, INDIA - VANKARA, ANU PRASANNA; MANNELA, HEMALATHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
The Indian bull frog, Hoplobatrachus tigerinus Daudin was found to be parasitized with the digenean, Tremiorchis ranarum Mehra et Negi. During an investigation of helminth parasites of amphibians from several localities of YSR district, Andhra Pradesh, this parasite was recovered from the intestine of the host. The morphological and diagnostic characteristics of Tremiorchis ranarum was studied by means of light microscopy, scanning electron microscopy along with its pathological effects on the host intestinal tissues to assess the extent of damage caused by them. Histopathogical effects include destruction of intestinal villi, inflammatory fibrosis, inflammation of villi at the site of attachment of parasite, hyperplasia and metaplasia, vacuolation of sub-mucosal cells and degeneration of intestinal layers due to proliferative changes. The pathological effects also include an increase in the thickness and the damage to mucosa.